SELEKSI DAN KAPASITASI SPERMATOZOA DENGAN METODE PERCOLL GRADIENT VKYUK FERTILISASI OOSIT DAN PRODUKSIEMBRIO IN VITRO PADA SAPI - Endang Triwulanningsih; MR Toelihere; TL Yusuf; B Purwantara; K Diwyanto; JJ Rutledge (Research Center for Biology-Indonesian Institute of Sciences, 2002)
This research has been conducted at the laboratory of in vitro fertilization of the University ofWisconsin, USA. These embryos may be used for improving genetic value of Indonesian cattle. Ovaries were collected from slaughterhouse in Wisconsin. Oocytes were matured in TCM-199 medium enriched with FSH 10 ı estradiol 17 P lul/ml and 10 % FCS for 20 hours. The oocytes were fertilized in vitro with motile sperm selected and capacitated by using the percoll gradient with 2 ml vs 0.5 ml per layer as treatment A and B respectively. Sperm and oocytes were incubated in fertilization medium (mTALP) for 20 hours. All zygotes were cultured in CRlaa medium up to btastocyst stage and were fed with serum 5 50 )j.l in culture medium on day 6. Percentages of cleavage, morula, blastocyst, expanded blastocyst, unfertilized and degenerated ova in this study were 86.3 vs 91.6 %, 53.3 % vs 75.9 %; 32.6 % vs 63.4 %; 21.1 % vs 33.0 %; 13.7 % vs 8.4 %, 32.9% vs 15.6 % for treatment A (n=1007) vs B (n=1055), respectively. Based on result of this study, it is concluded that the best method for IVP (in vitro production) of cattle embryos is using percoll gradient with 500 ul per layer.